Biogeochemical states, rates, and exchanges exhibit linear responses to large nutrient load reductions in a shallow, eutrophic urban estuary - Jeremy M. Testa; Walter R. Boynton; Casey L. S. Hodgkins; Amanda L. Moore; Eva M. Bailey; Johanna Rambo (Limnology and Oceanography, 2022)
We examined responses of water‐column conditions, sediment‐water fluxes, ecosystem metabolism, and nutrient export in the Back River estuary during the past three decades following multiple phases of nutrient load reductions from a large wastewater treatment plant. Total nitrogen (TN) loads from the treatment plant declined from 7000 kg N d −1 in the mid‐1980s to 1500 kg N d −1 following the implementation of enhanced nutrient removal in late 2017. Total phosphorus (TP) loads declined by ~90% from peaks in the mid‐1980s–1990s and have been stable ever since. In response, TN and TP concentrations measured since 1985 show declines that generally mirror that of loads from the treatment plant, and box model computations suggest significant reductions in nutrient export to adjacent Chesapeake Bay. As a consequence, water‐column chlorophyll a (Chl a ) concentrations have declined modestly over the record, despite inter‐annual variability. This reduction in Chl a coincided with a reduced frequency of nitrogen and phosphorus concentrations that would saturate phytoplankton growth, as well as reductions in ecosystem gross primary production and respiration derived from high‐frequency oxygen time‐series. Sediment‐water fluxes of dissolved nitrogen, phosphorus, and oxygen, as well as associated sediment concentrations of nitrogen, phosphorus, and carbon also declined over the record. These temporal patterns were reproduced in a 35‐yr model simulation that suggests a relatively rapid response to reduced organic matter deposition changes. Finally, the recycling of ammonium for a given TN load declined substantially, consistent with high observed rates of denitrification, indicating that well‐mixed estuaries can recover relatively rapidly in response to nutrient remediation.